Model Arrhennius Untuk Memprediksi Penyimpanan Kelapa Parut Kering - Guyup Mahardhian Dwi Putra; Diah Ajeng Setiawati (Universitas Muhammadiyah Mataram, 2021)
Dry grated coconut is a processed coconut product that can be directly used by consumers without requiring further processing. In order for dried coconut products to last longer, a good storage process is needed. Storage is intended to maintain the value of the stored commodity. One of the models used for estimating shelf life is the Arrhenius model. Parameters in this study were water content, temperature and humidity. Temperature parameters consisted of three treatments,i.e 30°C, 35°C and 40°C. The results showed a decrease in water content data obtained by using the Arrhenius method at each storage temperature for a temperature of 30°C that is 103.9 days, a temperature of 35°C is 74 days and a temperature of 40oC is 60.5 day.